Kontribusi (Indian Ocean Rim Association) IORA Dalam Memberdayakan Poros Maritim Indonesia Melalui Blue Economy - Aulya Ananda; Ruben Binsar; Nasywa Izra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article analyzes the contribution of the Indian Ocean Rim Association (IORA) to the development of the Blue Economy in Indonesia. As the largest archipelago, Indonesia has abundant marine resources, but their contribution to the national GDP is still not optimal. President Joko Widodo introduced the grand strategy of the Global Maritime Fulcrum (PMD) in 2014, which aims to optimize all of the country's marine potential. This study examines how Indonesia's leadership in IORA during the 2015-2017 period served as a strategic forum for safeguarding its national maritime interests. A descriptive qualitative approach was used in analyzing this research, using Institutional Liberalism theory to describe how IORA contributes as a regional strategic forum, as well as Epistemic Infrastructure to analyze the importance of science and technology in supporting maritime security and economic growth. The results of the study show that IORA serves as a strategic platform for Indonesia in its efforts to strengthen maritime diplomacy, develop blue economy cooperation, prevent IUU Fishing, and improve marine resource management. The Jakarta Concord and IORA Blue Carbon Hub demonstrate how international cooperation can strengthen the vision of the world's maritime axis and enhance Indonesia's status as an important actor in the maritime governance of the Indian Ocean region.Â